Enhancing Child Development through Senam Profil Pelajar Pancasila: A Case Study in Indonesian Early Childhood Education - Karwati, Tati; Nurhayati, Sri (Jurnal Ilmiah Profesi Pendidikan, 2024)
This study examines the Senam Profil Pelajar Pancasila (SPPP) program, an innovative early childhood education initiative in Indonesia that integrates physical development with cultural and moral education. Utilizing a qualitative case study approach at TK Darussalam, the research involved observations and interviews with teachers, administrators, and parents. The program aims to extend beyond physical development, emphasizing cultural identity and moral values. Despite challenges such as movement complexity and diverse learning needs, SPPP has shown positive impacts on children's kinesthetic intelligence, motor skills, and socio-emotional development. This research fills a gap in empirical studies on integrated educational programs, aligning with contemporary educational paradigms that advocate for holistic development. The findings suggest that SPPP is an effective model for comprehensive early childhood education, highlighting the importance of combining physical activities with cultural and moral education. This study contributes significant insights to the field, underscoring the potential of such integrative approaches in diverse educational contexts.